2017
DOI: 10.4103/ijpvm.ijpvm_324_16
|View full text |Cite
|
Sign up to set email alerts
|

Imminent angiotensin-converting enzyme inhibitor from microbial source for cancer therapy

Abstract: Background:Drugs targeting Angiotensin I-converting enzyme (ACE) have been used broadly in cancer chemotherapy. The recent past coupled with our results demonstrates the effective use of ACE inhibitors (ACEi) as anticancer agents, and they are potentially relevant in deriving new inhibitors.Methods:Bacterial strains were isolated from cow milk collected in Coimbatore, Tamil Nadu, India and plated on nutrient agar medium. The identity of the strain was ascertained by 16s rRNA gene sequencing method and was subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…It may be a potential therapeutic drug and need researches to test and verify. However, for Angiotensin Converting Enzyme (ACE)-Inhibitory, whether it has an anti-tumor effect is still unclear, some recent studies had demonstrated that Angiotensin Converting Enzyme (ACE) Inhibitory could induce apoptosis of cancer cell 69,70 . But some studies also demonstrated that it might increase the risk of canceryy 71 .…”
Section: Discussionmentioning
confidence: 99%
“…It may be a potential therapeutic drug and need researches to test and verify. However, for Angiotensin Converting Enzyme (ACE)-Inhibitory, whether it has an anti-tumor effect is still unclear, some recent studies had demonstrated that Angiotensin Converting Enzyme (ACE) Inhibitory could induce apoptosis of cancer cell 69,70 . But some studies also demonstrated that it might increase the risk of canceryy 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the physical and psychosocial domains of HRQoL were negatively associated with female gender, which is consistent with previously published research. 42 Female gender is associated with worse HRQoL despite controlling for potential confounding factors, such as sociodemographic variables (e.g., age, income, and education, among others). 42 Illness duration was negatively associated with the physical domain, consistent with previously published studies that found a negative association between the duration of chronic health conditions and HRQoL scores.…”
Section: Discussionmentioning
confidence: 99%
“…42 Female gender is associated with worse HRQoL despite controlling for potential confounding factors, such as sociodemographic variables (e.g., age, income, and education, among others). 42 Illness duration was negatively associated with the physical domain, consistent with previously published studies that found a negative association between the duration of chronic health conditions and HRQoL scores. 43 Chronic health conditions, such as diabetes and arthritis, result in loss of HRQoL as time progresses.…”
Section: Discussionmentioning
confidence: 99%
“…It also provides important information for improving HPV vaccine uptake in other jurisdictions, including the US and Canada, where programs are not meeting their targets. 22,23…”
Section: Introductionmentioning
confidence: 99%